Gênero, agroecologia e relação cidade-campo: políticas públicas e construção da soberania alimentar em Goiás - Nóbrega, Stéfanny da Cruz (2022)
This dissertation deals with the role of peasant women in the production of men's food and the repercussions of their work to guarantee the Food and Nutritional Security of the peasant family, as well as the horizon of construction of Food Sovereignty from the city-countryside relationship. To this end, the main methodological steps of the research are: 1) the survey on the themes, concepts and categories: Peasantry, Agroecology, Short Circuits of Commercialization, Territory, Work, Gender and Public Policies; 2) survey of statistical data, having as main sources: Ipea, IBGE, CPT, Diee, Mapa and Conab; 3) field work: in the municipalities of Goiânia, Aragoiânia, Bela Vista de Goiás, Silvânia, Vianópolis, Campestre de Goiás, Palmeiras de Goiás and Guapó. Thus, the research was structured from the spatial clipping of 10 experiences carried out by women in agroecological networks in Goiás, which welcomed us into their territories for conversations and transversal walks. The Territory analysis category was developed as central, for these experiences represented, in practice, the resistance to the territorialization of agribusiness, so that they are located in different conflicts. We also adopted a category of analysis, given the need to understand how women as political subjects, located in a context of pressure, exploitation and whose work is made invisible. The search for instruments to record the presence of women in the Agricultural Census is recent, and the absence of data reflects the absence of public policies that meet specific demands. In view of this, the research understood that women are the protagonists of an agroecological transition process that generates effects for female self-determination, for the permanence of families on the land and for access to men in the city. However, the process has resisted in the midst of solid networks and neoliberal contexts, in the face of a dismantling context. A presents the challenges and conducts public research for policy formulation.